Pengaruh Literasi Keuangan dan Faktor Demografi Terhadap Keputusan Investasi Mahasiswa FE Universitas Sarjanawiyata Tamansiswa - Muhammad Ahkam Al-Aziz; Risal Rinofah (J-MAS (Jurnal Manajemen dan Sains), 2021)
This study aims to find out the influence of financial literacy and demographic factors such as gender, generation year and income on student investment decisions at the Faculty of Economics Sarjanawiyata Tamansiswa University. Respondents to this study numbered 100 students from FE UST class of 2017 to 2020. The method used in this research uses quantitative methods. While the data analysis method used, among others descriptive analysis, validity and reliability test, and multiple regression test with the help of SPSS 20 program. The results of this study show that financial literacy has a significant positive effect on investment decisions. However, on demographic factors only the year of the force has a significant positive effect on investment decisions. While the year of force and income has no significant positive effect on investment decisions.